Pueblo Bonito - Pepper, George H.; Stuart, David E. (Albuquerque : University of New Mexico Press, 1996)
One of the most spectacular ruins in North America is Pueblo Bonito, located at Chaco Canyon in northwestern New Mexico. This book, originally published in 1920 and unavailable for decades, describes the earliest archaeological investigations of Pueblo Bonito. The excavations at Bonito, begun a century ago, in 1896, were overseen by the American Museum of Natural History, which published Pepper's book. To celebrate a century of archaeology at Pueblo Bonito the book is reissued with a preface that provides context for archaeologists and visitors to Chaco.
Originally published: New York : American Museum of Natural History, 1920.
Includes bibliographical references and index.
71468
Keywords: Pueblo Indians -- Antiquities; Pueblo Indians -- Material culture; Excavations (Archaeology) -- New Mexico -- Chaco Canyon National Historical Park; Pueblo Bonito Site (N.M.); Chaco Canyon National Historical Park (N.M.) -- Antiquities